2020
DOI: 10.1186/s13098-020-00545-z
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular volume status predicts body fluid response to SGLT2 inhibitor dapagliflozin in diabetic kidney disease

Abstract: Background: Sodium-glucose cotransporter 2 (SGLT2) inhibitors are an antihyperglycemic drug with diuretic action. We recently reported that the SGLT2 inhibitor dapagliflozin ameliorates extracellular volume expansion with a mild increase in urine volume. However, the impact of the pretreatment extracellular volume status on the body fluid response to SGLT2 inhibitors remains unclear. Methods: Thirty-six diabetic kidney disease (DKD) patients were treated with dapagliflozin. The body fluid volume, including int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 29 publications
2
43
1
Order By: Relevance
“…Another study investigating the effects of SGLT2 inhibitors in acutely hospitalized patients found no events of DKA in patients treated with empagliflozin, with one occurrence of DKA in the placebo group; there was no imbalance in volume depletion events between the two treatment groups 64 . Outcome trials have also showed consistent and robust benefits of SGLT2 inhibitors on kidney outcomes with no increase in the risk of AKI, 22,69 and experimental studies suggest that the effect of dapagliflozin on fluid status may also be favourable, thereby reducing the risk of precipitating acute renal impairment 38,70 . Nevertheless, we have implemented robust measures in the DARE‐19 study to minimize possible risks, such as exclusion of patients at higher risk of DKA (type 1 diabetes or history of DKA), daily measurements of acid‐base balance and kidney function during hospitalization, and frequent independent assessment of safety events by the IDSMC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study investigating the effects of SGLT2 inhibitors in acutely hospitalized patients found no events of DKA in patients treated with empagliflozin, with one occurrence of DKA in the placebo group; there was no imbalance in volume depletion events between the two treatment groups 64 . Outcome trials have also showed consistent and robust benefits of SGLT2 inhibitors on kidney outcomes with no increase in the risk of AKI, 22,69 and experimental studies suggest that the effect of dapagliflozin on fluid status may also be favourable, thereby reducing the risk of precipitating acute renal impairment 38,70 . Nevertheless, we have implemented robust measures in the DARE‐19 study to minimize possible risks, such as exclusion of patients at higher risk of DKA (type 1 diabetes or history of DKA), daily measurements of acid‐base balance and kidney function during hospitalization, and frequent independent assessment of safety events by the IDSMC.…”
Section: Discussionmentioning
confidence: 99%
“…64 Outcome trials have also showed consistent and robust benefits of SGLT2 inhibitors on kidney outcomes with no increase in the risk of AKI, 22,69 and experimental studies suggest that the effect of dapagliflozin on fluid status may also be favourable, thereby reducing the risk of precipitating acute renal impairment. 38,70 Nevertheless, we have implemented robust measures in the DARE-19 study to minimize possible risks, such as exclusion of patients at higher risk of DKA (type 1 diabetes or history of DKA), daily measurements of acid-base balance and kidney function during hospitalization, and frequent independent assessment of safety events by the IDSMC. These measures will permit appropriate assessment of the benefit-risk balance of dapagliflozin in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptomatic hyponatremic patients exhibit subtle disturbances in gait that improve following correction of the serum Na+ concentration [20,21]. A clinical study showed that the SGLT2 inhibitors are not merely a diuretic agent that generally uniformly reduces the body fluid volume regardless of the baseline fluid status, specifically the fluid response to dapagliflozin varies depending on the baseline volume fluid status [22]. Therefore, SGLT2 inhibitors exert different diuretic actions from loop diuretics and vasopressin V2 receptor antagonists and may induce a novel clinical benefit that may support the safety with low risk of fluid shortage when administering SGLT2 inhibitors to patients without fluid retention [22].…”
Section: Circulating Volumementioning
confidence: 99%
“…In a study of 30 patients with type 2 diabetes and kidney disease, those with a high ratio of bioimpedance measured extracellular weight to total body weight (> 0.4) showed significantly greater reductions in extracellular body weight with dapagliflozin administration compared to those with a low ratio (≤ 0.4); this association was not noted with administration of loop diuretics (≤ 0.4). (12) In the RECEDE-CHF trial, a randomized controlled trial of empaglifozin in patients with diabetes and heart failure treated with loop diuretics, empagliflozin use was associated with an approximate 500 ml/day increase in urine volume compared to placebo. (13) This increase in urine output with SGLT2i use occurred within a day of drug initiation and was sustained at 6 weeks.…”
mentioning
confidence: 99%